Kajian Atraksi, Aksesibilitas, Amenitas dan Ancilliary pada Kawasan Strategis Pariwisata di Kabupaten Wonosobo - Zam Zam Masrurun; Arina Nindyar Saraswati; Hardiman Hardiman; Atika Nur Hidayah; Andreas Yogi Prasetyo (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
This study examines the condition of attractions, accessibility, amenities, and ancillary services within the Strategic Tourism Area of Kertek, Wonosobo Regency. Using a descriptive qualitative approach supported by field observations, interviews, and secondary document analysis, the research provides an integrated assessment of tourism components that shape the area’s development potential. Findings reveal that the region possesses a strong concentration of natural, special-interest, agro-tourism, and cultural–religious attractions, forming a diversified tourism landscape. Accessibility is supported by national and regional road networks, although local village roads and public transport connectivity remain limited. Amenities are primarily concentrated in urban corridors, resulting in service gaps in rural areas where key attractions are located. Ancillary support involving government agencies, local communities, and private actors is present but requires stronger institutional coordination to ensure cohesive governance. The study concludes that the Kertek tourism area holds substantial potential to strengthen Wonosobo’s tourism competitiveness. However, maximizing these potential demands improvements in intra-area connectivity, equitable distribution of visitor facilities, and enhanced collaborative governance to support sustainable tourism development.